Hacked : A Radical Approach to Hacker Culture and Crime - Steinmetz, Kevin F. (Book collections on Project MUSE., 2016)
Public discourse, from pop culture to political rhetoric, portrays the figure of the hacker distinctly: a deceptive, digital villain. But what do we actually know about hackers? In Hacked, Kevin F. Steinmetz explores what it means to be a hacker and the nuances of hacker culture. Through extensive interviews with hackers, observations of hacker communities, and analyses of hacker cultural products, Steinmetz demystifies the figure of the hacker and situates the practice of hacking within larger political and economic structures of capitalism, crime, and control. This captivating book challenges many of the common narratives of hackers, suggesting that not all forms of hacking are criminal and, contrary to popular opinion, the broader hacker community actually plays a vital role in our information economy. Hacked thus explores how governments, corporations, and other institutions attempt to manage hacker culture through the creation of ideologies and laws that protect powerful economic interests. Not content to simply critique the situation, Steinmetz ends his work by providing actionable policy recommendations that aim to redirect focus from the individual to corporations, governments, and broader social issues. A compelling study, Hacked helps us understand not just the figure of the hacker but also digital crime and social control in our high-tech society.-- Back cover.